Development of Innovative Component for the Region’s Economic Security - Golova, Irina Markovna; Sukhovey, Alla Filippovna (Economy of Regions, 2017)
This article studies the development of innovative component for the region’s economic security. The hypothesis of the study is that in the context of globalization and development of network society, innovation is becoming one of the key elements ensuring the economic security of a region. We considered the relationship between the concepts of sustainable development and economic security. The authors show that currently, the economic security of the country directly depends on its place within the innovation chain. We substantiate that Russian Federation and its regions need to shift to the innovation development based on strengthening its own sources for long-term growth. The paper considers the basic theoretical and methodological problems in the formation of innovation component of the Russian regions’ economic security. We reveal the major essence and elements of the innovative component of the sustainable economic development of the region. The authors show that the formation of the innovative component of the region’s economic security demands the correlation of the strategy of regional innovation development and the production and technological type of territory. Additionally, this strategy should correlate with the desirable ways of production type transformation in the future, considering the trends of the world economy. We have highlighted the production and technological types of Russian regions as well as identified the features of relevant regional components for the innovation system of the Russian Federation to ensure sustainable development. The study defines the priority directions and goals for the development of economic security innovative component in the Russian regions. The authors’ calculations allowed to select a group of territorial subjects of the Russian Federation, which appear to be the most promising for the development of innovative activities for the elaboration of export-oriented high-tech industries. The results of this research can be used to improve the management of innovation activity and ensure the economic security of the Russian regions.